2008
DOI: 10.1038/nmat2340
|View full text |Cite
|
Sign up to set email alerts
|

Power-law scaling and fractal nature of medium-range order in metallic glasses

Abstract: The atomic structure of metallic glasses has been a long-standing scientific problem. Unlike crystalline metals, where long-range ordering is established by periodic stacking of fundamental building blocks known as unit cells, a metallic glass has no long-range translational or orientational order, although some degrees of short- and medium-range order do exist. Previous studies have identified solute- (minority atom)-centred clusters as the fundamental building blocks or short-range order in metallic glasses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
291
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(317 citation statements)
references
References 31 publications
22
291
2
2
Order By: Relevance
“…On the contrary, some studies have demonstrated that plenty of structural information is hidden behind the data of structure factors or PCFs, for example, a global packing containing both spherical-periodic order and local translational symmetry has been revealed by analysing PCFs of many metallic glasses 9 . A fractal nature of medium-range order in metallic glasses was also found by examining the relationship between the first peak position in structure factors and atomic molar volumes in many metallic glasses 7 . In fact, the oscillation in the structure factors or PCFs is an indication that a certain order does exist in amorphous solids 7 .…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…On the contrary, some studies have demonstrated that plenty of structural information is hidden behind the data of structure factors or PCFs, for example, a global packing containing both spherical-periodic order and local translational symmetry has been revealed by analysing PCFs of many metallic glasses 9 . A fractal nature of medium-range order in metallic glasses was also found by examining the relationship between the first peak position in structure factors and atomic molar volumes in many metallic glasses 7 . In fact, the oscillation in the structure factors or PCFs is an indication that a certain order does exist in amorphous solids 7 .…”
mentioning
confidence: 89%
“…Although significant progress has been made and provided insights into the atomic-level structure and short-to-mediumrange order in glasses [3][4][5][6][7][8][9][10][11][12][13][14] , the way of leading to the mediumrange order is still unclear [5][6][7][8][9][10] . Does a universal rule exist that nature follows to construct a glass structure as what has been discovered for crystals?…”
mentioning
confidence: 99%
“…Mechanical failure of metallic glasses continues to fascinate researchers [1][2][3][4][5], since dislocations, grain boundaries, crystallographic planes, etc., are not defined in this class of non-crystalline materials [6][7][8][9]. Instead, the shear transformation zone (STZ), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of such structures has been found in metallic glass formers [14][15][16] , where the presence of quasi-crystalline clusters with a few topological defects has been detected by diffraction techniques, such as atomic-scale high-resolution transmission electron microscopy and by X-ray, neutron and electron diffraction. An enhanced degree of topological order may be achieved via structural rearrangements, either by annealing below the glass transition temperature (physical aging) 17 or pressurizing 18 , which permits the nucleation of MRO regions in proximity to the quasi-crystalline clusters and the consecutive propagation of a similarly ordered structure.…”
mentioning
confidence: 99%